2019
DOI: 10.1002/lary.28095
|View full text |Cite
|
Sign up to set email alerts
|

Imaging findings in pediatric single‐sided deafness and asymmetric hearing loss

Abstract: Objective To examine the imaging findings on computer tomography (CT) and magnetic resonance imaging (MRI) in pediatric single‐sided deafness (SSD) and asymmetric hearing loss (ASH). Methods The medical records of 189 pediatric patients with SSD and ASH were retrospectively reviewed, and imaging findings were compared. SSD was defined as unilateral profound hearing loss and contralateral normal hearing ear. In the ASH group, ASHw was defined as the worse hearing ear with profound hearing loss, while ASHb was d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
2

Year Published

2020
2020
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
1
8
2
Order By: Relevance
“…In both studies, cochlear nerve deficiency was detected in 50% of the cases, and even 100% of the infants [43], showing that cochlear nerve deficiency is a common cause of UHL, especially in severe to profound congenital UHL. In addition to cochlear nerve deficiency, cochlear dysplasia and an enlarged vestibular aqueduct were detected as structural malformations which could explain the UHL [42]. Investigations of structural malformations are clinically relevant for the evaluation of the etiology of the hearing loss.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In both studies, cochlear nerve deficiency was detected in 50% of the cases, and even 100% of the infants [43], showing that cochlear nerve deficiency is a common cause of UHL, especially in severe to profound congenital UHL. In addition to cochlear nerve deficiency, cochlear dysplasia and an enlarged vestibular aqueduct were detected as structural malformations which could explain the UHL [42]. Investigations of structural malformations are clinically relevant for the evaluation of the etiology of the hearing loss.…”
Section: Discussionmentioning
confidence: 99%
“…Anatomical T1/T2 neuroimaging A study by Lipschitz et al [42] examined structural neuroimaging scans (CT and MRI) of 170 pediatric patients (age 0-18 years) with UHL. They reported that in nearly half of the sample, structural malformations were detected that could be associated with the hearing loss.…”
Section: Structural Plasticitymentioning
confidence: 99%
“…Etiological evaluation is a crucial step toward better management with an effective counseling process for patients and parents. Magnetic resonance imaging is an important diagnostic tool that also helps in informed therapy planning [14]. Unfortunately, up until now, there is no supporting evidence for the efficacy of MVD of the vestibulocochlear nerve for SNHL.…”
Section: Discussionmentioning
confidence: 99%
“…While several past studies have evaluated CND in pediatric patients with UHL, the literature has reported widely variable prevalence of CND ranging from 9 to 50% [Clemmens et al, 2013;Nakano et al, 2013;Paul et al, 2017;Usami et al, 2017;van Beeck Calkoen et al, 2017;Lipschitz et al, 2020;Pollaers et al, 2020;Tahir et al, 2020]. Evaluation of CND in pediatric patients with AHL has been limited in the literature, with studies reporting a range of 0-28% prevalence of CND [Usami et al, 2017;Lipschitz et al, 2020]. Of note, studies that have compared CND prevalence in both UHL and bilateral pediatric HL have demonstrated significantly higher rates of CND in UHL (39-50%) as compared to bilateral HL (5%) [Nakano et al, 2013;Pollaers et al, 2020].…”
Section: Introductionmentioning
confidence: 99%